Legal Sanctions Against Perpetrators Criminal Persecution That Resulted Serious Injury (Case Study Medan District Court Decision No. 000/ Pid.Sus/2022/Pn.Mdn) - Azmi, Syariful; Kusbianto, Kusbianto; Zuliah, Azmiati; Fitriana, Fitriana (Legalpreneur Journal, 2023)
Criminal acts of persecution it is a form of action that can harm others that is against the physical. One of them that can cause serious injury or it can even cause loss of life somebody.The act occurred the factors include less public behavior well controlled due to low level of education and environmental influences, less Association good that eventually resulted disputes both personal and groups. Problems that appointed in this study are how is the application of criminal law against the crime of persecution this resulted in severe injuries in The Samarinda District Court and what to consider judge's decision to drop verdict against criminal acts the resulting persecution serious injuries in court (Case Study Medan District Court Decision No. 000/ Pid.Sus/2022/Pn.Mdn